2021
DOI: 10.1037/edu0000533
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear relations between achievement and academic self-concepts in elementary and secondary school: An integrative data analysis across 13 countries.

Abstract: It is well-documented that academic achievement is associated with students' self-perceptions of their academic abilities, that is, their academic self-concepts. However, low-achieving students may apply self-protective strategies to maintain a favorable academic self-concept when evaluating their academic abilities. Consequently, the relation between achievement and academic selfconcept might not be linear across the entire achievement continuum. Capitalizing on representative data from three large-scale asse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 78 publications
(178 reference statements)
0
17
0
Order By: Relevance
“…Second, ensuring that latent variables are invariant across countries and levels at the same time is, to our best knowledge, currently only possible via fixing the parameters of the measurement models for each country data set. This fixed-parameter approach may deteriorate model fit and introduce some bias to the structural parameters (Scherer & Nilsen 2016), but because the state-of-research indicates that this bias may be considerably small (Devlieger & Rosseel, 2019), we consider the SAM approach a promising alternative for analyzing large-scale educational data (Keller et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, ensuring that latent variables are invariant across countries and levels at the same time is, to our best knowledge, currently only possible via fixing the parameters of the measurement models for each country data set. This fixed-parameter approach may deteriorate model fit and introduce some bias to the structural parameters (Scherer & Nilsen 2016), but because the state-of-research indicates that this bias may be considerably small (Devlieger & Rosseel, 2019), we consider the SAM approach a promising alternative for analyzing large-scale educational data (Keller et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We followed the Cheung and Jak (2016) approach to quantify and explain between-country variation, that is, the SAM approach. In this approach, the large-scale data are first split into different samples—in our study, the countries (Keller et al, 2020). Second, the analytic models of interest are specified, estimated, and evaluated for each sample—in our study, the multilevel structural equation models with the fixed parameters in the measurement models.…”
Section: Methodsmentioning
confidence: 99%
“…The studies cited above on the latent structure of LSAs clearly identified general ability factors in addition to domain-specific abilities. However, these findings did not change practices within the psychometric community involved in the construction and scaling of LSAs, nor in the education academic research and policy communities that analyze and interpret LSA data for research and to inform policy making (e.g., Borgonovi & Pokropek, 2019;Deng & Gopinathan, 2016;Jakubowski & Pokropek, 2015;Keller et al, 2020). Measurement frameworks in education do not consider the relevance of g. Brunner (2008) notes that analyses of students' characteristics and domain-specific ability scores reported in LSAs, meta-analyses, and reviews have relied almost entirely on the standard model of domain-specific abilities.…”
Section: The Bifactor Modelmentioning
confidence: 94%
“…Such research opportunities involve in-depth meta-analyses of policy-relevant subgroups, for example, to provide reliable empirical evidence of the consistency and generalizability of the magnitude of gender differences among top-performing students (i.e., the top 5%) in mathematics (Keller et al, 2021). Likewise, IPD meta-analyses of ELSAs allow researchers to examine the generalizability of (novel) theoretical propositions across countries, for example, to test predictions about nonlinear relationships between achievement and academic self-concepts (Keller et al, 2020), relationships between innovative school environments and teaching practices (Blömeke et al, 2021), relationships between epistemic beliefs and educational outcomes in science (Guo et al, 2021), year-in-school effects on academic selfconcept (Marsh, 2016), or, as we illustrate in the present paper, how gender differences in students' achievement are moderated by their SES (see Else-Quest & Hyde, 2016).…”
Section: Advantages Of Combining Meta-analytic Techniques and Ipd From Elsasmentioning
confidence: 99%
“…However, meta-analytic models have only rarely been applied to results from ELSAs in general (e.g., Else-Quest et al, 2010; and to IPD from ELSAs in particular (e.g., Blömeke et al, 2021;Gray et al, 2019;Keller et al, 2020Keller et al, , 2021Nowell & Hedges, 1998). 1 Why?…”
Section: Advantages Of Ipd Meta-analyses Of Elsasmentioning
confidence: 99%